Religion, Forgiveness and Humanity. (16th September 2015) - Hamilton, Christopher
Abstract : There are many ways of doing philosophy of religion. No doubt all of them have need of abstract concepts and passages where reflection is more technical than it usually is, say in everyday thought and reflection. But it is well known that, in this area of philosophy, and not only in this area of philosophy, abstract reflection can run the risk of losing contact with the ins and outs, the finer-grained details, of the lived experience of reality. One way to seek to reduce this risk is to approach abstract or general reflection through philosophical reflection on specific cases. This is what I intend to do in this paper. My aim is to explore in detail a specific and, in my view, extraordinarily striking example, in this case, an example of forgiveness in a religious, indeed, Christian context, drawing out where possible general or abstract conclusions, but seeking always to root reflection in the specific case in order to understand better from a philosophical point of view what is at stake, what is important, when thinking about the issue in question. Of course, I shall be seeking primarily to elucidate philosophically the example I shall discuss, but, by implication, I hope that the kinds of questions, worries and concerns I discuss might raise consciousness – philosophical consciousness – of the kinds of questions that we might explore in other examples, specifically those which involve forgiveness in a religious context.